(untitled) (Ozone Therapy Global Journal, 2019)
Introduction and Objectives: In recent years, the ophthalmology field has experienced a concept transformation with the arising of Neuropathic Ocular Pain, practically unknown to the medical community. The optimal therapies for this disease are still under study. The Ocular Pain, such as the rest of the body, can be of the Nociceptive or Neuropathic type. Chronic Neuropathic Ocular Pain can significantly compromise these patient’s quality of life. It has been discovered that certain cases of Dry Eye are associated with Neuropathic Ocular Pain. Conventional therapies for Dry Eye Disease, do not provide relief in all patients with Neuropathic Ocular Pain, especially those with symptoms of hyperalgesia and photoalodynia. Therefore, it is urgent to have new therapeutic tools, effective for this entity. In this study we present a case of a 29-year-old female patient, diagnosed with Neuropathic Ocular Pain, showing complete resolution of Dry Eye symptoms with over than 6 months of evolution, refractory to conventional treatments, treated with periocular injections of Medicinal Ozone, subcutaneously and Procaine. Conclusions: Ozone Therapy and Procaine, subcutaneously, are easy to apply by the ophthalmologist, effective and without side effects, so the therapeutic options for Neuropathic Ocular Pain cases can be increased, when not responding to conventional treatments, opening an interesting field of research in this area.